Intralesional Triamcinolone Diacetate In the Treatment of Keloids and Hypertrophic Scars—Use of the Dermo-Jet - Sam D. Theogaraj; Mani M. Mani (Indian Journal of Plastic Surgery)
1. The history of steroids in the treatment of keloid is reviewed.